Surely surely Marisol Rainey - Kelly, Erin Entrada 1977- (Maybe Marisol, 2022)
"One of Marisol's least-favorite things is gym class--especially when Coach Decker announces that they will be playing kickball--so Marisol and her best friend Jada ask the best (and stinkiest) athlete they know--Marisol's big brother Oz--for help"--